2018
DOI: 10.1002/aic.16164
|View full text |Cite
|
Sign up to set email alerts
|

Novel aeration of a large‐scale flat sheet MBR: A CFD and experimental investigation

Abstract: Having previously established that the hydrodynamic effect introduced by slug bubbles is more effective and economic in fouling amelioration in flat sheet MBRs (FSMBR) than conventional bubbling, this work is focused on its implementation in a commercial FSMBR. The overall objective is to enhance the hydrodynamic effect on fouling control through the use of two‐stage large‐sized bubble development (coalescence and split). Computational Fluid Dynamics (CFD) was used to predict hydrodynamic features and substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…For example, PIV is widely used throughout the chemical industry for the study of ow eld distributions in stirred tank reactors, 24 at gas-evolving electrodes, 25 in bubble columns 26 and at sheet MBR. 27 For example, Liu et al 28 have used PIV to investigate the hydrodynamic characteristics of two-phase ow elds at gas-evolving electrodes, whilst Leslie et al 29 used PIV to determine the ow states in an aerated bench scale MBR.…”
Section: Introductionmentioning
confidence: 99%
“…For example, PIV is widely used throughout the chemical industry for the study of ow eld distributions in stirred tank reactors, 24 at gas-evolving electrodes, 25 in bubble columns 26 and at sheet MBR. 27 For example, Liu et al 28 have used PIV to investigate the hydrodynamic characteristics of two-phase ow elds at gas-evolving electrodes, whilst Leslie et al 29 used PIV to determine the ow states in an aerated bench scale MBR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous electrochemical experiments had showed that shear stress from over 60 mL slug bubble could produce excellent spanwise sheer stress of more than 1.0 Pa on the flat membrane [12]. Having established that the hydrodynamic effect introduced by slug bubbles is more effective and economic in fouling amelioration between two membranes in flat sheet MBRs (FSMBR) than conventional bubbling, our recent work has been focused on its implementation in a commercial-scale FSMBR [13,14], consisting of 100 membranes of the size normally used in industry. Recently a novel slug bubble production method has been developed through a two-stage process of bubble coalescence above the aerator followed by bubble splitting to 'feed' a number of channels [13].…”
Section: Introductionmentioning
confidence: 99%
“…Having established that the hydrodynamic effect introduced by slug bubbles is more effective and economic in fouling amelioration between two membranes in flat sheet MBRs (FSMBR) than conventional bubbling, our recent work has been focused on its implementation in a commercial-scale FSMBR [13,14], consisting of 100 membranes of the size normally used in industry. Recently a novel slug bubble production method has been developed through a two-stage process of bubble coalescence above the aerator followed by bubble splitting to 'feed' a number of channels [13]. This has proven to be fundamental to the implementation of slug bubbling hydrodynamics to large-scale FSMBRs [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations